2018
DOI: 10.5505/pajes.2018.77910
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy logic based intelligent autonomous vehicle control system design in the TORCS game environment

Abstract: Bu çalışmada TORCS (The Open Racing Car Simulator) oyun ortamında bulanık mantık tabanlı otonom araç kontrol sistemi tasarımı yapılmıştır. Bu çalışmadaki amaç, aracın yol bariyerlerine çarpasını engelleyerek hiçbir zarar almadan ve yol sınırları içerisinde kalmasını sağlayarak pistin dışına çıkmadan yarışı tamamlamasıdır. Bu bağlamda, aracın otonom bir şekilde ilerleyebilmesi için bulanık mantık ve klasik kontrol yapılarından oluşan akıllı bir sistem geliştirilmiştir. Aracın vites geçişleri otomatik hale getir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…As noted by Chen et al (2021), the advantage of PID controllers is their ability to reduce computational load; this particular characteristic is significant for vehicles operating at high speeds. Recent studies have implemented customized PID controllers for high-speed longitudinal control systems (Gomes et al, 2017;Wang et al, 2018;Chen et al, 2020Chen et al, , 2021, lateral (steering) control systems (Armagan & Kumbasar, 2017;Zhang et al, 2018), and at least one previous study by Wang et al (2021) has utilized two PID controllers for both longitudinal and lateral control. Generally, the results of these works found that PID controllers provided favorable results for simulated racing vehicles.…”
Section: Applications Of Pid Controllers For Simulated Vehiclesmentioning
confidence: 99%
“…As noted by Chen et al (2021), the advantage of PID controllers is their ability to reduce computational load; this particular characteristic is significant for vehicles operating at high speeds. Recent studies have implemented customized PID controllers for high-speed longitudinal control systems (Gomes et al, 2017;Wang et al, 2018;Chen et al, 2020Chen et al, , 2021, lateral (steering) control systems (Armagan & Kumbasar, 2017;Zhang et al, 2018), and at least one previous study by Wang et al (2021) has utilized two PID controllers for both longitudinal and lateral control. Generally, the results of these works found that PID controllers provided favorable results for simulated racing vehicles.…”
Section: Applications Of Pid Controllers For Simulated Vehiclesmentioning
confidence: 99%
“…S. E. Ovur et al solved the inverted pendulum problem with a fuzzy logic system [13]. E. Armağan and T. Kumbasar designed a fuzzy system for autonomous vehicle control [14]. A. Yılmaz et al performed a risk analysis for cancer disease using the fuzzy logic method [15].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these aspects, researchers have tested their self-driving car systems in games as they provide dynamic, cheap, realistic, and convenient testbeds. In this context, various self-driving car systems have been proposed that are tested in racing game environments such as The Open Racing Car Simulator (TORCS) (Armagan and Kumbasar, 2017; Wang and Liaw, 2015), JavaScript Racer (Yu et al, 2016), VDrift (Kehrle et al, 2011), and World Rally Championship 6 (Perot et al, 2017). Kehrle et al, (2011) designed a nonlinear model predictive control that uses model mismatch between the physical model and an approximate coarser model.…”
Section: Introductionmentioning
confidence: 99%
“…Kehrle et al, (2011) designed a nonlinear model predictive control that uses model mismatch between the physical model and an approximate coarser model. In Armagan and Kumbasar (2017), a fuzzy logic-based autonomous vehicle control system has been designed for the TORCS environment. In this structure, a fuzzy logic-based throttle/brake control system has been implemented to make the car capable to accelerate/decelerate in a realistic manner at desired velocity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation